Analisis Growth Ratio dan Leverage Terhadap Nilai Perusahaan Pada Emiten Property dan Real Estate di BEI Periode 2021-2025 - Andi Nuratika; Darwis Darwis; Damirah Damirah; Besse Faradiba (Al-Buhuts, 2026)
Investor choose to invest in companies that can send positive signals to them. Therefore, one of the most frequently observed indicators is a company’s value, as reflected by stock price that is higher than the book value. This research was conducted to analyze the influence of the growth ratio proxied by sales growth (SG), and leverage proxied by debt-to-equity ratio (DER) on the firm value of property and real estate issuers listed on the Indonesia Stock Exchange (IDX) from 2021-2025. The population consists of 79 property and real estate companies in the capital market, which was subsequently narrowed down to 57 issuers after excluding companies in the special monitoring category research data spanning 5 years. The sampling technique used was purposive sampling and selecting 30 companies with the sampling criteria: listed before 2021, complete financial reports, not delisted for more than 6 months, and having revenue. The analytical method used is regression analysis of panel data with the help of application Eviews 12. The results of the T-test indicate that SG and DER do not have a significant effect on PBV. The results of the F-test also indicate that the independent variables in this study do not have a significant effect. This indicates that, both individually and collectively, the research models do not yet sufficiently explain tha variation in PBV for the 2021-2025 period. Investors in this sector employ risk-based investment strategies that prioritize issuers cash flow resilience and real liquidity capacity over responding to fluctuations in accounting profits from sales growth or capital structures deemed reasonable as a consequence of the capital-intensive nature of the industry.